Persons living with HIV infection on antiretroviral therapy also consulting traditional healers: a study in three African countries. (September 2017) - Wanyama, Jane N; Tsui, Sharon; Kwok, Cynthia; Wanyenze, Rhoda K; Denison, Julie A; Koole, Olivier; van Praag, Eric; Castelnuovo, Barbara; Wabwire-Mangen, Fred; Kwesigabo, Gideon P; Colebunders, Robert
Traditional healers provide healthcare to a substantial proportion of people living with HIV infection (PLHIV) in high HIV burden countries in sub-Saharan Africa. However, the impact on the health of retained patients visiting traditional healers is unknown. In 2011, a study to asses adherence to anti-retroviral therapy (ART) performed in 18 purposefully selected HIV treatment centers in Tanzania, Zambia and Uganda showed that 'consulting a traditional healer/herbalist because of HIV' was an independent risk factor for incomplete ART adherence. To identify characteristics of PLHIV on ART who were also consulting traditional healers, we conducted a secondary analysis of the data from this study. It was found that 260 (5.8%) of the 4451 patients enrolled in the study had consulted a traditional healer during the last three months because of HIV. In multivariable analysis, patients with fewer HIV symptoms, those who had been on ART for >5.3 years and those from Tanzania were more likely to have consulted a traditional healer. However, at the time of the study, there was a famous healer in Manyara district, Loliondo village of Tanzania who claimed his herbal remedy was able to cure all chronic diseases including HIV. HIV treatment programs should be aware that patients with fewer HIV symptoms, those who have been on ART for five or more years, and patients attending ART centers near famous traditional healers are likely to consult traditional healers. Such patients may need more support or counseling about the risks of both stopping ART and poor adherence. Considering the realities of inadequate human resources for health and the burden of disease caused by HIV in sub-Saharan Africa, facilitating a collaboration between allopathic and traditional health practitioners is recommended.